Factors Associated With Newly HIV Infection and Transmitted Drug Resistance Among Men Who Have Sex With Men in Harbin, P.R. China - Hui, Shan; Chen, Fangfang; Li, Yi; Cui, Yan; Zhang, Jinhui; Zhang, Ling; Yang, Yisi; Liu, Yanlin; Zhao, Yashuang; Lv, Fan (Frontiers in Public Health, 2022)
Background This study aimed to evaluate HIV incidence, factors associated with HIV sero- conversion and transmitted drug resistance (TDR) among newly infected men who have sex with men (MSM) in Harbin, P.R. China. Methods A cohort study was conducted among MSM in Harbin during 2013 and 2018, with a follow-up frequency of every 6 months. Blood samples from MSM were tested for HIV antibodies, RNA was extracted from plasma, and the pol gene was sequenced, and genotypic drug-resistance analyses were performed. Results From 2013 to 2018, the overall rate of HIV incidence was 3.55/100 PY. Syphilis infection, unprotected sex with men in the past 6 months, and having no knowledge of HIV/AIDS were risk factors for HIV seroconversion. The distribution of HIV genotypes was as follows: CRF01_AE, 57.1%; CRF07_BC, 28.5%; CRF55_01B, 2.0%; B, 8.2%. The prevalence of transmitted drug resistance was 4.08 %. Conclusion HIV incidence in MSM in Harbin is moderately high, and transmitted drug resistance exists in the population.